Upaya Meningkatkan Kemampuan Bermain Estimasi Melaluimetode Eksperimen Pada Kelompok Asemester IDI TK Muslimat Nu Punggursugih Kecamatan Ngawen Kabupaten Bloratahun 2015/2016 - Ulfatun Nikmah, Siti; , Drs. Surtikanti, M.Pd (2015)
Experimental activities is an interesting methodand fun for young children which can develop estimates. The reality that occurs in learning activities in kindergarten are still many teacher who use methods that monotonous in developing the ability to play the estimation. This research aims to improve childrens ability to play estimastion through experimental activities. This reserach is a classroom research. The subject of this study is a learning group A in TK NU Muslimat Punggursugih, Ngawen District, Blora Regional in Academic Year 2015/2016. This research is a classroom research (PTK) with the working prosedure 2 (two) cycle consist of four stage : planning, action, observation, reflection. Methods of data collection using observation, fieldnotes, and documentation. The result showed an increase in the estimated play. Research shows that the average estimates play before the action is 42, 25%. After learning by conducting experiment in the first cycle increasing 69,88%. In cycle played estimates increased to 80,80%. Overall, di experimental activities can improve the estimation Group A in TK Muslimat NU Punggursugih.